Studi In Vitro : Aktivitas Antijamur Kulit Buah dan Daun Coffea canephora Terhadap Candida albicans - Mastuti Widianingsih; Yesi Afrida Aini (Journal of Pharmaceutical and Sciences, 2026)
Candida albicans is a major cause of invasive candidiasis with high morbidity and mortality rates, and it has shown increasing resistance to antifungal agents. The objective of this research to evaluate the antifungal activity of Coffea canephora peel and leaf extract against Candida albicans in vitro by determining the Minimum Inhibitory Concentration (MIC). Robusta coffee peel and leaves were extracted using maceration with 96% ethanol, followed by phytochemical screening and antifungal activity testing using the broth dilution method. Phytochemical screening revealed the presence of alkaloids, phenolic-tannins, flavonoids, saponins, and terpenoids, while steroid were not detected. Based on the antifungal activity test conducted separately, both extracts had the same MIC value at a concentration of 12,5%. Statistical analysis using One Way ANOVA demonstrated a significant difference among treatment groups (p<0,05). The antifungal activity of the extract is presumed to be associated with phenolic compounds, such as chlorogenic acid and caffeine, which may act through disruption of cell membrane integrity and inhibition of ergosterol synthesis. These finding suggest that Coffea canephora peel and leaf extract has the potential to be further developed as an antifungal agent, especially in topical formulations, but further toxicity tests and in vivo tests are required.